S-Layer Glycoprotein From Lactobacillus kefiri Exerts Its Immunostimulatory Activity Through Glycan Recognition by Mincle - Malamud, Mariano; Carasi, Paula; Assandri, Matías H.; Freire, Teresa; Lepenies, Bernd; Serradell, María de los Ángeles (Frontiers in Immunology, 2019)
The development of new subunit vaccines has promoted the rational design of adjuvants able to induce a strong T-cell activation by targeting specific immune receptors. The S-layer is a (glyco)-proteinaceous envelope constituted by subunits that self-assemble to form a two-dimensional lattice that covers the surface of different species of Bacteria and Archaea. Due to their ability to self-assemble in solution, they are attractive tools to be used as antigen/hapten carriers or adjuvants. Recently, we have demonstrated that S-layer glycoprotein from Lactobacillus kefiri CIDCA 8348 (SLP-8348) enhanced the LPS-induced response on macrophages in a Ca2+-dependent manner, but the receptors involved in these immunomodulatory properties remain unknown. Therefore, we aim to determine the C-type lectin receptors (CLRs) recognizing this bacterial surface glycoprotein as well as to investigate the role of glycans in both the immunogenicity and adjuvant capacity of SLP-8348. Here, using a mild periodate oxidation protocol, we showed that loss of SLP-8348 glycan integrity impairs the cell-mediated immune response against the protein. Moreover, our data indicate that the adjuvant capacity of SLP-8348 is also dependent of the biological activity of the SLP-8348 glycans. In order to evaluate the CLRs involved in the interaction with SLP-8348 an ELISA-based method using CLR–hFc fusion proteins showed that SLP-8348 interacts with different CLRs such as Mincle, SingR3 and hDC-SIGN. Using BMDCs derived from CLR-deficient mice, we show that SLP-8348 uptake is dependent of Mincle. Furthermore, we demonstrate that the SLP-8348-induced activation of BMDCs as well as its adjuvant capacity relies on the presence of Mincle and its signalling adaptor CARD9 on BMDCs, since SLP-8348-activated BMDCs from Mincle-/- or CARD9-/- mice were not capable to enhance OVA-specific response in CD4+ T cells purified from OT-II mice. These findings significantly contribute to the understanding of the role of glycans in the immunomodulation elicited by bacterial SLPs and generate a great opportunity in the search for new adjuvants derived from non-pathogenic microorganisms.